Biofertilizer and chemical fertilizer induced changes in cyto-morphological and biochemical constituents of Foeniculum vulgare Mill. - Kumar, Girjesh; Singh, Rajani; Mishra, Radha (Current Botany, 2020)
The agriculture sector requires a revolutionary alternative that makes crop production high and elicits less ill-effects on the environment. At present, agriculture area facade the challenge of low yield of many agronomic crops which lead to economic losses. Experimentally, it is proved that fertilizer use can boost yield two three times more in spite of other factors unchanged. But surplus and unbalanced usage of these soil supplements like fertilizers and irrigation causes serious problems to our soils like water logging and formation of saline soils and ultimately lead to denatured soil. This situation can be alleviated through the use of eco-friendly biofertilizer. So the present appraisal scrutinizes the effect of fertilizer Ammonium Phosphate Sulphate (APS) and biofertilizer (Agrozyme) on the cytology, morphology and pigment constituents of the Foeniculum vulgare Mill. and to trace out a safer crop enhancer among the two. The results revealed that fertilizer expelled to be more chromotoxic and mito-inhibitory at higher concentration in comparison to biofertilizer. Fertilizer negatively affects the plant’s mitotic index while biofertilizer enhances mitotic index parallel to the increasing concentration. Biofertilizer shows positive effect on the germination, survival and plant growth while fertilizer shows this elevation effect at lower concentration. The biochemical constituents (photosynthetic pigments) are greatly affected by higher concentration of both the treatments. The treated system shows various anomalies such as stickiness, precocious movement, loop formation at metaphasic stage and stickiness, laggard and bridge etc at anaphasic stage. Since, biofertilizers area much safer as compared to fertilizers and it also enhances the qualitative and quantitative traits, therefore it could be used in agro-system to obtain sustainable crop upgradation.